1998
DOI: 10.1029/97ja02296
|View full text |Cite
|
Sign up to set email alerts
|

Two spacecraft observations of a reconnection pulse during an auroral breakup

Abstract: Abstract. At 1130 UT on November 28, 1995, two spacecraft, Interball-Tail and Geotail, were in a favorable position to study the plasma sheet activity and an auroral breakup observed on the ground near the spacecraft ionospheric footpoints. Both spacecraft were near the neutral sheet, and they were nearly aligned along the magnetic meridian. During the auroral breakup observed at the equatorward half of the auroral oval (also registered as an AKR burst at Interball) both spacecraft

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 27 publications
4
60
0
Order By: Relevance
“…Concerning the role of reconnection and its location, our results agree with those of Petrukovich et al (1998), who determined the location of the reconnection site during the pseudobreakup to be rather close to the Earth (at ∼16 R E ). Nagai et al (1998) also reported on the reconnection event which started at X > −15R E during the pseudobreakup.…”
Section: Comparison With Previous Observationssupporting
confidence: 82%
“…Concerning the role of reconnection and its location, our results agree with those of Petrukovich et al (1998), who determined the location of the reconnection site during the pseudobreakup to be rather close to the Earth (at ∼16 R E ). Nagai et al (1998) also reported on the reconnection event which started at X > −15R E during the pseudobreakup.…”
Section: Comparison With Previous Observationssupporting
confidence: 82%
“…Even the substructure of characteristically pulsed dayside reconnection on 5-10 min time scales (i.e. flux transfer events) are well-resolved in dayside flow data as pulsed ionospheric flows (Lockwood et al, 1989(Lockwood et al, , 1993Elphic et al, 1990;Pinnock et al, 1993Pinnock et al, , 1995Moen et al, 1995;Provan et al, 1998;Neudegg et al, 1999Neudegg et al, , 2000Milan et al, 2000;Wild et al, 2001). As a consequence, there is now little uncertainty about the central role of magnetopause reconnection in magnetospheric dynamics and flow excitation.…”
Section: Introductionmentioning
confidence: 96%
“…Lui, 1991Lui, , 1996Frank and Sigwarth, 2000;Friedrich et al, 2001). Nevertheless, recent results from the Geotail spacecraft do show that reconnection typically begins in the dusk sector plasma sheet at down-tail distances of ∼20-30 R E , a few minutes before the onset of expansion signatures on the ground, and then expands to encompass a significant fraction of the dusk and midnight sector tail (Nagai et al, 1998; Nagai and Machida, 1998; Petrukovich et al, 1998;Machida et al, 1999). Both initial dipolarization and the convection that results from tail reconnection contribute to substorm-associated Dungey-cycle flux transport in the tail.…”
Section: Introductionmentioning
confidence: 99%
“…Further elaboration of this hypothesis resulted in creating space weather forecasting tools based on local-linear filters (Price et al, 1994;Vassiliadis et al, 1995;Valdivia et al, 1996), data-derived analogues (Klimas et al, 1997;Horton et al, 1999), and neural networks (Hernandes et al, 1993;Gleisner and Lundstedt, 1997;Weigel et al, 2002). The low dimensional organized behavior of the magnetosphere on global scales is also evident in many in situ observations of the large-scale features of substorms by many spacecrafts including INTERBALL and GEOTAIL missions (Petrukovich et al, 1998;Nagai et al, 1998;Ieda et al, 1998).…”
Section: Introductionmentioning
confidence: 99%